PENERAPAN STANDAR PROSES DALAM PEMBELAJARAN MATEMATIKA OLEH GURU YANG SUDAH DAN BELUM BERSERTIFIKAT PENDIDIK DI SMP KABUPATEN PINRANG - Iqbal Mukaddas (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2019)
This study aims to describe the Application of Process Standards (planning, implementation, assessment) in mathematics learning by teachers who have been certified educators and who have not. The instruments used in this study are (1) learning planning (checklist and interview guide), (2) implementation process (observation sheet and interview guide), and (3) process assessment (checklist sheet and interview guide). The subject of this research is 6 mathematics subject teachers, which is divided into 3 teachers who have and 3 teachers who have not Certified Educator. The results of this research are (1) Application of process standard in mathematics learning by teachers who have already certified educator on (a) learning planning administration stated Good, (b) learning activity on application of professional competence by subject Teachers 1, Teacher 2 and Teacher 3 obtain category Fine, on the application of pedagogic competence by the subjects Teachers 1, Teachers 2 and Teachers 3 obtain the Very Good Rating category. (2) Application of process standard in mathematics learning by teachers who have not been certified educator on (a) learning planning administration stated Good, (b) learning activity on application of professional competence by subject of Teachers 5 and Teacher 6 obtained Good category and Teacher 4 obtained category Enough Good.